POLIGAMI SIRI TANPA IZIN ISTRI PERTAMA (Studi Kasus Di Desa Lebak Mantan Kecamtan Muara Wis Kabupaten Kutai Kartanegara) - Muhammad Haidir Ali Khafid; Abdullah Afif (Kampus Akademik Publiser, 2024)
Marriage is a necessity of life for all people since ancient times, now, and in the future until the end of time. Therefore, marriage is a problem that is always present in society and in legal matters. The issue most discussed in the marriage sphere is polygamy. Polygamy is indeed very controversial, there is one side that rejects polygamy based on various kinds, both normative, psychological and many even link it to the emergence of gender inequality. For the people of Lebak Mantan Village, polygamy is a form of marriage carried out by a husband who remarries another woman. In Lebak Mantan Village there are several people who carry out siri polygamous marriages without the permission of the first wife, for several reasons which will trigger curiosity and open the question: What is the view of the people of Lebak Mantan village towards siri polygamy without the permission of the first wife, what are the factors that cause polygamy to occur? siri without the first wife's permission in Lebak Mantan Village, and what is the juridical and Islamic law view of siri polygamy without the first wife's permission. This research is descriptive qualitative research using field or empirical studies. In obtaining data, the author used three data collection techniques, namely interviews, observation and documentation. Meanwhile, in the analysis used are techniques for data reduction, presentation and drawing conclusions. Based on the results of research in the field, the community in Lebak Mantan Village views that polygamy is always seen as something that is not good and must be avoided because it causes more harm, and the factors that cause siri polygamy to occur are: wealth, friendship environment, sexual desire, weak law enforcement, convenience. access to information, weak religious knowledge, and not having the courage to give permission to the first wife, resulting in several factors such as polygamy occurring in the former Lebak village. Then the Juridical View and Islamic Law towards Siri Polygamy Without the Permission of the First Wife, it is clear from a juridical view and Islamic Law that both prohibit carrying out siri polygamy without the permission of the first wife, from a juridical view there are several regulations that clearly prohibit the existence of siri polygamy without the permission of the first wife, Likewise, in Islamic law there are several reasons that make serial polygamy without the permission of the first wife strictly prohibited and must be avoided.